Linking Lean Adoption and Implementation in Healthcare to National Cultures - Rodrigo E. Peimbert-García; Tapani Jorma; Leopoldo Eduardo Cárdenas-Barrón; Nucamendi-Guillén, Samuel; Heriberto García-Reyes (My University, 2021)
Lean Healthcare (LHC) is a widely accepted approach to improve the quality of care around the world. This research compares two studies, which evaluated the adoption/implementation of LHC in Finland and Mexico, to understand how cultural similarities/differences influence LHC implementations. Data were gathered from previous questionnaire-based studies administered to healthcare professionals in both countries. Statistics (X2, p, and Wilcoxon tests) are used to compare both studies across topics related to adoption, introduction, integration, success, and barriers of LHC projects, and results are linked to cultural dimensions. Driven by economic savings, LHC has been more adopted in Finland than in Mexico (75/13%). Upon introduction, similarities are found in the way LHC projects are conducted, high project success rate, poor level of integration, and enabling/disabling factors. Conversely, differences were mainly found in the objectives of implementing LHC. These similarities/differences are linked to national factors involving culture, social structure, uncertainty management, time orientation, and indulgence level. In particular, uncertainty avoidance, equal rights’ structure, and a feminine culture are positive for implementing Lean. These findings can be a benchmark to evaluate cultural practices. Thus, this study provides insight into how national cultures relate to LHC and determined distinctive sociotechnical aspects that influence its adoption/implementation.